Implementasi Program IPPNU Waluyo dalam Pembinaan Pelajar - Sastiyagustin Eka Devi; Agus Salim Chamidi; Agus Nur Soleh (IAINU Kebumen, 2023)
IPPNU Waluyo or Nahdlatul Ulama Youth Association in Waluyo Village is a religious organization that actively carries out routine and incidental work programs. One of the goals is to control student activity. There are many factors that lead students or teenagers to do activities that deviate and are far from the prevailing norms, making this organization directly control student activities through various work programs. Even though this organization is in the community, it has a big impact on the lives of students or teenagers. It is important for education not only to rely on learning materials but also important to foster student morale in socializing with fellow humans and other living creatures. The research approach used is qualitative, using a field research design. The process of data collection is done by means of observation, interviews and documentation. The data obtained from the informants were then analyzed by means of data reduction, data presentation and then conclusions were drawn. To provide guidance to students in Waluyo Village, IPPNU Waluyo is using a work program that has been determined to be carried out together. Among them are routine programs, namely Lapanan, Hadroh, Deresan and Pilgrimage to the graves of prominent figures in the village. The annual program is Pilgrimage in Buluspesantren District towards Ramadan and village gatherings. The incidental program is in the form of the participation of this organization in helping the implementation of community activities such as the birthday of the prophet, isro mi'raj, khataman and others. Fostering students to do good activities, be involved in the community and have good character. IPPNU Waluyo in providing guidance to students in Waluyo Village, this is through scheduled programs with religious and social nuances.